(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this article, the importance of competencies in the organization of the primary education system, the theoretical and practical foundations of the formation of competencies, the study of standards in the field of education of developed foreign countries, the qualitative renewal of the primary education system, as well as the improvement of the teaching methodology, It is explained about the step-by-step implementation of the principles of individualization in the educational process, technological literacy, critical thinking and creativity competencies with the possibility of applying acquired competencies in independent life, and the wide introduction of effective forms, methods and tools to the educational process based on national, universal and spiritual values.